Impact of Economic Instability on The Arabic Teachers' Productivity on Lessons Delivery in Higher Islamic Schools in Nigeria: Impact of Economic Instability on The Arabic Teachers' Productivity on Lessons Delivery in Higher Islamic Schools in Nigeria - Ahmad Garba; Iskandi; Dody Irawan; Anis Shalatin Simon; Suharia Sarif (Institut Agama Islam Negeri Syaikh Abdurrahman Siddik Bangka Belitung, 2026)
This research, titled